1981
DOI: 10.1128/aac.20.5.576
|View full text |Cite
|
Sign up to set email alerts
|

Cefazolin and moxalactam pharmacokinetics after simultaneous intravenous infusion

Abstract: A high-performance liquid chromatographic method for the measurement of moxalactam concentrations in serum was modified to permit the simultaneous measurement of both moxalactam and cefazolin. We then studied whether the simultaneous administration of both moxalactam and cefazolin to nornal subjects would produce profiles of serum concentration versus time which were the same as those obtained after the administration of each drug individually. Six healthy adults received a 30-minfusion of cefazolin (10 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
0
9
1
Order By: Relevance
“…The advantages of simultaneous administration of two antimicrobial agents for comparative studies of their tissue penetration have been identified recently (8). Half as many subjects are required for the same number of datum points (tissue concentrations), pairing of all data permits the use of more powerful statistical tests, many complicating factors are eliminated (e.g., differences in time of removal of tissue), concentrations of both drugs can be measured simultaneously if high-performance liquid chromatographic assay is available, and an antibiotic with relatively poor activity against a specific pathogen (e.g., moxalactam versus Staphylococcus aureus [3]) can still be studied when given with a reliable prophylactic agent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantages of simultaneous administration of two antimicrobial agents for comparative studies of their tissue penetration have been identified recently (8). Half as many subjects are required for the same number of datum points (tissue concentrations), pairing of all data permits the use of more powerful statistical tests, many complicating factors are eliminated (e.g., differences in time of removal of tissue), concentrations of both drugs can be measured simultaneously if high-performance liquid chromatographic assay is available, and an antibiotic with relatively poor activity against a specific pathogen (e.g., moxalactam versus Staphylococcus aureus [3]) can still be studied when given with a reliable prophylactic agent.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of moxalactam and cefazolin in serum were determined simultaneously by a high-performance liquid chromatographic assay according to the method of Diven et al (2), modified as previously described (8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major differences in moxalactam pharmacokinetics seen in the elderly appear to be related to diminishing renal function and highly variable nonrenal elimination. Creatinine clearance can be used in estimating moxalactam doses in the elderly without significant renal impairment, but recommendations for the use of serum creatinine as an estimation of renal function or drug half-life are not valid in this population group.The pharmacokinetic properties of moxalactam, a 1-oxabeta-lactam antibiotic, have been studied in children (19,22,23), normal adults mostly under the age of 60 (7,11,15,21,24,26,28), and patients with renal disease (1-3, 12-14, 18, 29). Because moxalactam is primarily eliminated unchanged by the kidney, a decrease in renal function associated with disease or aging should lead to an alteration in the elimination of the drug.…”
mentioning
confidence: 99%
“…The pharmacokinetic properties of moxalactam, a 1-oxabeta-lactam antibiotic, have been studied in children (19,22,23), normal adults mostly under the age of 60 (7,11,15,21,24,26,28), and patients with renal disease (1-3, 12-14, 18, 29). Because moxalactam is primarily eliminated unchanged by the kidney, a decrease in renal function associated with disease or aging should lead to an alteration in the elimination of the drug.…”
mentioning
confidence: 99%